On ``box'' models of shock acceleration and electron synchrotron spectra - Drury, Luke O'C.; Duffy, Peter; Eichler, David; Mastichiadis, Apostolos (Astronomy and Astrophysics, 1999)
The recent detection of high energy gamma -rays coming from supernova remnants and active galactic nuclei has revived interest in the diffusive shock acceleration of electrons. In the present paper we examine the basis of the so-called ``box'' model for particle acceleration and present a more physical version of it. Using this we determine simple criteria for the conditions under which ``pile-ups'' can occur in shock accelerated electron spectra subject to synchrotron or inverse Compton losses (the latter in the Thompson limit). An extension to include nonlinear effects is proposed.
Keywords: acceleration of particles; Astrophysics; gamma rays: theory; ISM: COSMIC RAYS; shock waves